Analysis of the Influence of Parental Knowledge and Attitudes on Children's Environmental Health Mitigation Behavior During the Dry Season in the City of Jakarta: A Case Study of Air Pollution - Dwi Atmanto; Sitti Nursetiawati (Dinasti International Journal of Education Management And Social Science, 2025)
Air quality in major cities like Jakarta harms health and the economy, particularly affecting children. Areas frequented by children, such as roads around schools and playgrounds, have especially concerning pollution levels. This study aims to investigate how parents' knowledge and attitudes towards reducing the effects of air pollution on children's health are related. A quantitative correlational survey was conducted among 75 parents of children aged 5-17 in Jakarta, particularly those residing near roads or high-pollution areas. The data was analyzed using SPSS. Key findings include (1) a significant correlation between parents' knowledge of air pollution and their efforts to lessen its impact on children's health (.000 < 0.05), (2) a connection between parents' attitudes and their efforts to mitigate health issues (.000 < 0.05), (3) a link between the desire to address air pollution and actual mitigation behavior (.000 < 0.05), and (4) the combined impact of knowledge, attitudes, and the desire to address air pollution on children’s health protection parental’s behavior (.000 < 0.05), contributing to 54.8% of the variance. Moreover, 90% of participants concurred that improving air quality is a shared responsibility, underscoring the necessity for public education on reducing air pollution to safeguard children's health.